SAS jungle survival - Davies, Barry (Skyhorse Publishing, 2013)
When we think of jungles, we often think of a densely forested area with thick foliage; this is what is known as a primary jungle. But jungles can also include swamps, grasslands, and cultivated areas. Primary jungles can fall into the category of either a tropical rain forest or a deciduous forest, depending on the types of trees and plants found growing there. A tropical rain forest is typified by having tall trees whose upper branches interlock to form canopies. Yet of all the environments in which man has to survive, the jungle offers the best chance. The SAS have operated in the jungle for years, sometimes staying in the forest for months at a time. They developed a technique whereby they had two sets of clothing, one for daytime use and one for night. Just before they went to sleep they would change from their wet clothing, which was normally hung under the shelter to dry out. In the morning they would change from their dry clothing and put on the wet. It is an uncomfortable change, but one that guaranteed a good night's sleep in dry clothing. The SAS Guide to Jungle Survival will teach the reader to come to terms with the jungle environment, understand it, and work with it as opposed to "fighting it." The jungle forest can provide shelter, food, and water in abundance, and this book will show you how. If the jungle offers any problems, it is with disease and wild animals; The SAS Guide to Jungle Survival will show you how to avoid and resist both and come out alive.